vonis pidana mati terhadap pelaku penembakan anggota polri oleh TNI - Ayu Winda Amelia Des Tifa Mahesa Ayu; I Ketut Seregig; Zainab Ompu Jainah (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the application of military criminal law and judges’ legal considerations in imposing the death penalty on a member of the Tentara Nasional Indonesia (TNI) who shot and killed members of the Kepolisian Negara Republik Indonesia (POLRI) based on the Decision of Pengadilan Militer I-04 Palembang Number 50-K/PM.I-04/AD/V/2025.Research Methodology: This study applies a normative and empirical juridical approach using a case approach. The research examines relevant regulations, including the Kitab Undang-Undang Hukum Pidana, Kitab Undang-Undang Hukum Pidana Militer, Undang-Undang Nomor 31 Tahun 1997 tentang Peradilan Militer, and Undang-Undang Darurat Nomor 12 Tahun 1951, supported by interviews with a Polisi Militer investigator and a military court judge. Data were analyzed qualitatively.Results: The findings show that premeditated murder was not proven because the act occurred due to panic and anger. However, the intentional shooting using an illegal firearm that caused three deaths fulfilled the elements of intentional killing under Article 338 of the Kitab Undang-Undang Hukum Pidana.Conclusions: The military justice system effectively enforced criminal accountability, demonstrating that TNI status does not eliminate legal responsibility.Limitations: This study is limited to one military court decision and a specific criminal case context.Contributions: This research contributes to military criminal law studies by providing insights into sentencing policies for serious crimes committed by TNI members.